Pengembangan Kompetensi Sumberdaya Aparatur Desa Melalui Strategi Capacity Building (Studi di Kantor Desa Bluru Kidul, Kecamatan Sidoarjo, Kabupaten Sidoarjo) - Niar Gita Ardani (Jurnal Administrasi Publik, 2015)
Abstract: The Village Officials’ Competence Development Through Capacity Building Strategy (Study In The Village Of Bluru Kidul, Sub-District Of Sidoarjo, Sidoarjo). Village officials’ resources competence development in the village office of the Bluru Kidul is needed to overcome the problems of imbalance population by the number of village officials and the lack of the number of computers for work device. The competence development is done through a capacity building strategy. Capacity building strategies based on role modeling aspect in Bluru Kidul village office that consist of resource of the village Officials that apply a friendly and courteous service, alert, and discipline. Based on the learning process approach aspect, the resources competence of Bluru Kidul Village officials is increasing because of the routine coaching and training. Some of the supporting factors are leadership, coordination among officials, innovation, and collaboration with the District Government. The inhibiting factors are budget, infrastructure, village officials’ responsibility (accountability), as well as the ability of village officials in the field of computer technology. Keywords: Capacity Building, Role Modelling, Learning Process Approach Abstrak: Pengembangan Kompetensi Sumberdaya Aparatur Desa Melalui Strategi Capacity Building (Studi di Kantor Desa Bluru Kidul, Kecamatan Sidoarjo, Kabupaten Sidoarjo). Pengembangan kompetensi sumberdaya aparatur desa di Kantor Desa Bluru Kidul dibutuhkan untuk mengatasi permasalahan ketidakseimbangan jumlah penduduk dengan jumlah aparatur desa serta kurangnya jumlah komputer untuk sarana bekerja. Pengembangan kompetensi dilakukan melalui strategi capacity building. Strategi capacity building berdasarkan aspek role modelling di Kantor Desa Bluru Kidul terdiri dari sumberdaya aparatur desa yang menerapkan pelayanan dengan ramah dan sopan, siap siaga, serta kedisiplinan. Berdasarkan aspek learning process approach, kompetensi sumberdaya aparatur Desa Bluru Kidul meningkat karena adanya pembinaan dan pelatihan secara rutin. Beberapa faktor pendukung terdiri dari kepemimpinan, koordinasi antar aparatur, inovasi, dan kerjasama dengan pihak Kecamatan. Faktor penghambatnya adalah anggaran, sarana dan prasarana, tanggung jawab aparatur desa (akuntabilitas), serta kemampuan aparatur desa di bidang teknologi komputer. Kata kunci : Capacity Building, Role Modelling, Learning Process Approach